Therapeutic potencial of mesenquimal stem cells in equine laminitis - Mendes, Ana Beatriz dos Santos (2021)
Laminitis is a very common disease in the clinical routine of horses, which causes, among other symptoms, pain and lameness, being an important cause of euthanasia. In this condition, there is a weakening of the connection between the horny case and the distal phalanx, resulting in the sinking and palmar / plantar rotation of this bone. Several mechanisms are involved in the pathogenesis of laminitis, which include vascular, enzymatic, traumatic, glucose deprivation and endocrinopathic theories, so that it can occur secondarily to several other diseases, such as colic and equine metabolic disease. However, the compression of the mechanisms that govern changes in the pathophysiology of this disease is quite complex, and is not yet fully understood. This factor limits the development of effective therapies for curing laminitis. The diagnosis can be made through the evaluation of the animal's history, clinical signs, physical examination and complementary exams, such as radiography, anesthetic blocks, venography, thermography, among other methods. Therapy should involve pain control and stabilization of laminar tissue, and varies according to the stage of development of the disease, especially the acute and chronic phases. Thus, regenerative medicine, which includes the use of mesenchymal stem cells, has gained considerable prominence in recent years, since it has a positive influence on the cure of various orthopedic injuries in horses.